Efektifitas Rinfogroups Sebagai Media Komunikasi Untuk Meningkatkan Keaktifan Mahasiswa Pada iLearning Plus - Fitriawati, Noura; Aini, Qurotul; Aristo, Nabila Cynthia (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
In this globalization era, the use of technology is very influential in every activity we do, including communication activities. Technology has provided so much convenience for us in communication, including communication in the field of education. At Raharja College, every student, staff, and lecturer is given a facility that can be used to communicate, an email called Rinfo. In addition, the Raharja College also provides an online learning system called iLearning +. With the online learning system, it requires an online communication media to accommodate communication between students and lecturers, so that the learning process can run effectively and efficiently. Therefore, the development of Rinfo Apps is very much needed as a communication medium on iLearning +. Rinfo group is a Google System that can be used as a communication medium in the iLearning + learning process. By creating a forum called the mailing list at Rinfo Group, students and lecturers can communicate easily and everywhere, lecturers can provide material, assignments, or other announcements through this mailing list, as well as students who can easily ask the lecturers . With this, indirectly can increase the activity of students. The authors used 2 (two) research methods, that are observation and literature study. The results of this study are a communication medium for students and lecturers on iLearning + which is expected to increase student activity in the online learning process.